2007
DOI: 10.1007/s10115-006-0050-6
|View full text |Cite
|
Sign up to set email alerts
|

Supervised tensor learning

Abstract: This paper aims to take general tensors as inputs for supervised learning. A supervised tensor learning (STL) framework is established for convex optimization based learning techniques such as support vector machines (SVM) and minimax probability machines (MPM). Within the STL framework, many conventional learning machines can be generalized to take n th -order tensors as inputs. We also study the applications of tensors to learning machine design and feature extraction by linear discriminant analysis (LDA). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
184
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 334 publications
(185 citation statements)
references
References 36 publications
1
184
0
Order By: Relevance
“…There have been a large number of data mining algorithms rooted in these fields to perform different data analysis tasks. The 10 algorithms identified by the IEEE International Conference on Data Mining (ICDM) and presented in this article are among the most influential algorithms for classification [47,51,77], clustering [11,31,40,[44][45][46], statistical learning [28,76,92], association analysis [2,6,13,50,54,74], and link mining.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a large number of data mining algorithms rooted in these fields to perform different data analysis tasks. The 10 algorithms identified by the IEEE International Conference on Data Mining (ICDM) and presented in this article are among the most influential algorithms for classification [47,51,77], clustering [11,31,40,[44][45][46], statistical learning [28,76,92], association analysis [2,6,13,50,54,74], and link mining.…”
Section: Discussionmentioning
confidence: 99%
“…Many researches have showed that representing the images as tensors of arbitrary order can further improve the performance of algorithms in most cases [18][19][20][21][22][23][24]. Consequently, how to generalize LRR to tensor learning is another interesting topic for future study.…”
Section: Discussionmentioning
confidence: 99%
“…These methods, such as tensor PCA [8], tensor LDA [9,10], tensor subspace analysis [11][12][13], treat original data as second-or high-order tensors. For supervised feature classification [14], the tensor factorization can lead to structured dimensionality reduction by learning multiple interrelated subspaces. Discriminant analysis using tensor representation [15] can avoid the curse of dimensionality dilemma and overcome the small sample size problem.…”
Section: Introductionmentioning
confidence: 99%